Corporate social responsibility: gender equality and the reconciliation of work and family life: a report on the experience of the Equality is Quality Award - Guerreiro, Maria das Dores (2012)
The purpose of this publication is to provide an account of the process leading to the allocation of the “Equality is Quality" Award, sponsored by the Commission for Equality in Labour and Employment (CITE) over the last five years, with the aim of encouraging corporate social responsibility in this area. This document benefits from the experience of a team, which has for several years analysed and assessed gender equality policies and practices in various organisations (companies, co-operatives and associations) and whose work has allowed it to gather information on the various typical situations described here. This document will also reflect upon the way in which employers have supported this initiative and proved to be aware of the problems of guaranteeing gender equality and reconciling work and family life.